2021
DOI: 10.2147/idr.s284455
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Carbapenemase-Producing Klebsiella pneumoniae Isolated from Egyptian Pediatric Cancer Patients Including a Strain with a Rare Gene-Combination of β-Lactamases

Abstract: Purpose Healthcare-associated infections caused by multi-drug-resistant (MDR) pathogens are a global threat. We aim to assess the clonal relatedness among carbapenemase-producing Klebsiella pneumoniae (CPKP) strains infecting Egyptian pediatric cancer patients. Materials and Methods Identification and antimicrobial susceptibility testing of 149 Gram-negative isolates obtained from pediatric cancer patients were performed by VITEK 2. Genes enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…Strikingly, carbapenem resistance was detected in 80.9% of the Enterobacterales isolates. This level of resistance is higher than recent studies in Egypt describing the isolation of CRE with the percentages 46% [ 26 ], 59% [ 27 ], 68.8% [ 28 ] from cancer patients and 48% from intensive care units [ 5 ]. In the study performed by Hassuna et al [ 29 ], very high frequency of carbapenem resistance (95%) was detected among the K. pneumoniae isolates.…”
Section: Discussionmentioning
confidence: 69%
“…Strikingly, carbapenem resistance was detected in 80.9% of the Enterobacterales isolates. This level of resistance is higher than recent studies in Egypt describing the isolation of CRE with the percentages 46% [ 26 ], 59% [ 27 ], 68.8% [ 28 ] from cancer patients and 48% from intensive care units [ 5 ]. In the study performed by Hassuna et al [ 29 ], very high frequency of carbapenem resistance (95%) was detected among the K. pneumoniae isolates.…”
Section: Discussionmentioning
confidence: 69%
“…By using the disc diffusion method and the broth microdilution method, respectively, the results showed that 65 (60.2%) and 91 (84.3%) of the isolates were meropenem resistant [47]. This percentage of resistance (84.3%) exceeds the percentages reported in recent Egyptian research documenting the isolation of CRE, which were 46% [48], 68.8% [49] 59% [50], from patients with malignancy, and 48% from ICUs [51]. In the study conducted by Hassuna et al it was found that 95% of the K. pneumoniae isolates were resistant to carbapenem [52].…”
Section: Multidrug-resistantmentioning
confidence: 71%
“…All isolates were positive for the OXA gene, 56 (93%) were positive for the VIM gene, 51 (85%) were positive for the NDM gene, 38 (63%) were positive for the IMP gene, and 10 (17%) were positive for KPC gene. In Egypt, the OXA gene was reported as the most predominant carbapenemase with no or low prevalence of the KPC gene in many studies between 2020 and 2022 [37] [39] . In contrast, Gandor et al .…”
Section: Discussionmentioning
confidence: 99%